Economic Policy and Theological Reflection in South Africa - Naudé, Piet J. (International journal of public theology, 2014)
After giving an overview of major economic policy developments and their successes or not in South Africa from its transition to democracy in 1994 until recently, this article acknowledges efforts at, but also pleads for stronger engagement of theology with economic issues. The article also highlights some of the difficulties in achieving this and gives guidelines that may assist in forging a closer link between theological reflection and economic policy formation/execution. It is suggested in particular that theologians embark on a more intentional and purposeful development of economic expertise by taking cognizance of the insights of economists. In this way public theology may move beyond mere formulations of visions of an economically just society and criticizing betrayals of that vision to a theology that employs thorough economic analyses to offer concrete suggestions for economic policy and economic practices. Such a public theology would contribute to addressing poverty, unemployment and inequality.